Synthesis and Evaluation of Coumarin-Chalcone Derivatives as α-Glucosidase Inhibitors - Hu, Chun-Mei; Luo, Yong-Xin; Wang, Wen-Jing; Li, Jian-Ping; Li, Meng-Yue; Zhang, Yu-Fei; Xiao, Di; Lu, Li; Xiong, Zhuang; Feng, Na; Li, Chen (Frontiers in Chemistry, 2022)
Coumarin and chalcone, two important types of natural products, both exist α-glucosidase inhibition activity. In this work, coumarin-chalcone derivatives 3(a~v) were synthesized, and their α-glucosidase inhibitory were screened. The results showed that all synthetic derivatives (IC50: 24.09 ± 2.36 to 125.26 ± 1.18 μM) presented outstanding α-glucosidase inhibitory activity than parent compounds 3-acetylcoumarin (IC50: 1.5 × 105 μM) and benzaldehyde (IC50: 9 × 105 μM) and the positive control acarbose (IC50: 259.90 ± 1.06 μM). Among them, compounds 3j, 3q, 3t displayed the highest α-glucosidase inhibitory activity (IC50: 30.30 ± 2.53, 29.74 ± 2.68, 24.09 ± 2.36μM, respectively)，which were ~10 times stronger than acarbose. The kinetic assay of 3j (KI = 11.02 μM, KIS = 21.39 μM), 3q (KI = 16.48 μM, KIS = 30.37 μM) and 3t (KI = 18.82 μM, KIS = 59.99 μM) revealed that these compounds inhibited α-glucosidase in a mixed-type manner. Molecular docking was used to simulated the interaction between α-glucosidase and compounds 3j, 3q, 3t.